FAKTOR BLOCKING DALAM BAHASA INGGRIS - I Wayan Ana; Made Subur (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
Word formation is a dynamic process that contributes significantly to vocabulary expansion. This study explores the various factors that hinder the formation of words in the English language. The research investigates linguistic elements that act as barriers to the organic growth of the lexicon. Linguistic factors encompass syntactic constraints, morphological irregularities, and phonological intricacies, which pose challenges to the seamless creation of new words. Additionally, the study delves into semantic ambiguities that impede the clear delineation of meanings, hindering the formation of concise and universally accepted terms. The method applied in this research is descriptive qualitative with the data taken from various resources. The theory applied for this research is the theory of Aronoff. Based on the result of analysis, it is found that blocking refers to the non-acceptance of a new word form not due to the violation of word formation rules but rather because of the existence of another simpler form that precedes it or has already been used for a different meaning. There are two types of blocking in English, namely type-blocking and token-blocking. Type-blocking involves the competition of regular morphological processes, while token-blocking is the potential blocking of regular forms by synonymous words that already exist. There are three conditions for token-blocking: synonymy, productivity, and frequency. Factors causing blocking in the formation of new words can be classified into four categories: phonological, morphological, semantic, and aesthetic.